2000
DOI: 10.1002/(sici)1098-2264(200006)28:2<220::aid-gcc11>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

A novel and consistent amplicon at 13q31 associated with alveolar rhabdomyosarcoma

Abstract: Rhabdomyosarcomas are the most common soft‐tissue sarcoma found in children. The alveolar subtype is clinically more aggressive than the embryonal subtype. In addition to the presence of specific chromosome translocations and associated fusion gene products in a high proportion of the alveolar subtype, we previously showed that tumors with this histology frequently show evidence of genomic amplification. Here, we substantially extended the number of alveolar rhabdomyosarcoma samples examined by comparative gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 32 publications
2
37
0
Order By: Relevance
“…None of the seven Ewing’s sarcomas contained GLI1 amplification [25]. Gordon et al [11] reported 28% of 44 primary tumors and six cell lines of alveolar rhabdomyosarcomas to contain amplified GLI1 gene. Analysis of 37 primary adult sarcomas by Stein et al revealed the absence of GLI1 amplification in this tumor cohort [26].…”
Section: Gli1 Gene Amplificationmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the seven Ewing’s sarcomas contained GLI1 amplification [25]. Gordon et al [11] reported 28% of 44 primary tumors and six cell lines of alveolar rhabdomyosarcomas to contain amplified GLI1 gene. Analysis of 37 primary adult sarcomas by Stein et al revealed the absence of GLI1 amplification in this tumor cohort [26].…”
Section: Gli1 Gene Amplificationmentioning
confidence: 99%
“…Human GLI1 gene amplification is also uncommon in most cancers even though it was initially identified as an amplified gene in a cancer cell line. However, the incidence rates for GLI1 amplification vary significantly with the highest frequency (28%) reported in alveolar rhabdomyosarcomas [11]. A number of polymorphic variants of the human GLI1 gene have been reported, with the majority of them localized within the non-coding regions.…”
Section: Introductionmentioning
confidence: 99%
“…One of the first studies on miRNAs expression in the clinical context of RMS focused on amplification of the 13q31-32 chromosomal region, which is amplified in a fraction of alveolar RMS patients [97] and includes the C13orf25 gene [98]. This gene contains the miR-17-92 cluster (miR-17, miR-19a, miR-19b, miR-20a, and miR-92), which is considered an onco-miR cluster in some tumor types and cross-talks with MYC , an oncogene amplified in about 20% of fusion-positive alveolar RMS.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly amplified genomic regions observed in PAX gene fusion–positive tumors are 2p24, containing the MYCN oncogene, and 12q13-q14, which includes CDK4 . 26 The amplification of MYCN , which occurs in 28% of fusion-positive cases, has been confined to a genomic region less than 1 Mb, including the same region frequently observed in neuroblastoma cases. 27 This region includes only 2 genes ( MYCN and DDX1 ) and is observed most commonly in PAX3 - FOXO1 fusion–positive RMS.…”
Section: Rms Geneticsmentioning
confidence: 99%
“…Other amplified regions in fusion-positive tumors include 15q24-26, 1p36, 13q31, 1q21, and 8q13-21. 26 The regions of 1p36, which encompasses the PAX7 locus, and 13q31, which includes MIR17HG , are associated specifically with PAX7-FOXO1 tumors.…”
Section: Rms Geneticsmentioning
confidence: 99%